Το καθολικό της Νέας Μονής Ζαλόγγου Αρχιτεκτονική και ζωγραφική - Καραλής, Ηλίας; Κουτρόπουλος, Γρηγόριος Χ. (Πρεβεζάνικα Χρονικά, 2017)
The monastery of Zalongo is located on the mountain called «Zalongo» in the region of Preveza in Epirus. St. Demetrios, which is the Katholikon of the monastery, is an instance of a variation of the type of single-aisled domed church. The church consists of nave, bema, and a narthex. The most interesting element of the church is that the dome is supported by four arches, which rest on two pairs of pilasters formed in the north and the south wall, through a part of a sphere. The iconographical program of the Κatholikon of Saint Demetrios in Zalongo dates to 1816 by the published inscription. The unpublished but restored program was executed by the artists Ioannis (priest) and his brother Christodoulos from Koritiani. The program reveals that the artists choose themes between the post-Byzantine northwestern workshop and the stylistics trends from others artists from the Katsanochoria region and Kapesovo village.